Spectroscopic and photodynamic properties of 5,10,15,20-tetrakis[4-(3-N,N-dimethylaminopropoxy)phenyl]porphyrin and its tetracationic derivative in different media - Mora, Sabrina Jimena (2013)
The spectroscopic properties and the photodynamic activity of 5,10,15,20-tetrakis[4-(3-N,N-dimethylaminopropoxy)phenyl]porphyrin (TAPP) and its tetracationic derivative (TAPP4+) were studied in homogeneous media and in microheterogeneous systems. The results were compared with those of 5,10,15,20-tetra(4-N,N,N-trimethylammoniumphenyl)porphyrin (TMAP4+), which represents an active tetracationic photosensitizer. Absorption and fluorescence studies indicated that the tetrapyrrolic macrocycle retains its individual spectroscopic properties. Interaction with β-cyclodextrin (β-CD) was found for TAPP4+ by fluorescence emission. Also, these porphyrins interact with n-heptane/sodium bis(2-ethylhexyl)sulfosuccinate (AOT)/water reverse micelles. Photosensitization ability was evaluated using 9,10-dimethylanthracene in N,N-dimethylformamide and AOT micelles, while tetrasodium 2,2′-(anthracene-9,10-diyl)bis(methylmalonate) was used in aqueous solutions. Also, photosensitized decomposition of l-tryptophan was investigated in these media. In particular, Trp was fast photooxidized by TAPP in a biomimetic media formed by AOT reverse micelles. Therefore, this intrinsically non-charged porphyrin represents an interesting photosensitizer for the photodynamic inactivation of microorganisms.